Tinjauan Kriminologi Terhadap Prilaku Menyimpang di Kalangan Remaja (Studi Kasus Pelanggaran Kelengkapan Berkenderaan di Sekolah Menengah Kejuruan Negeri Pertanian Terpadu Provinsi Riau - Herdianto Surya, Dwiky (EDUTECH CONSULTANT, 2017)
The researchers conducted a study entitled â€œDeviant Behavior Against Criminology Overview Among Teens(Violation Case Study Completed on the drive is Vocational School District Integrated Agricultural Riau Province)â€. This study formulates the problem or background factors of deviant behavior committed by young people (students) Vocational High School of Agriculture Riau province from the perspective of Criminology?. And the goal of this research is the students County Vocational School District Integrated Agricultural Riau using vehicles to transport them daily. The aim of this study was to describe the influence of personal factors, family factors and environmental conditions in accordance with the theory Lemerst regarding deviant behavior among young people (students) at the Vocational School District Integrated Agricultural Riau Province in 2016. This research method is quantitative by analyzing data obtained descriptive analysis of 75 adolescent respondents (students) that transport using vehicles.